ANALISA DAMPAK KEBIJAKAN PENURUNAN TARIF PAJAK PENGHASILAN (PPh) FINAL UNTUK UMKM TERHADAP PENERIMAAN PAJAK NEGARA DI KOTA BATAM PROV. KEPRI - Vanomy, Afrianti Elsye (FIA UB, 2021)
This study aims to determine whether MSMEs in Batam have implemented PP No. 23 of 2018 according to the form of business or business profile the impact of this rate reduction of this rate reduction on tax revenue at KPP Pratama Batam Selatan. Data obtained from distributing questionnaires via Google form and interviews and direct data collection at KPP Pratama Batam Selatan. The sampling method of this research is purposive sampling technique.andÂ uses descriptive quantitative by investigating the influence of the MSME business profile variable on State Revenue through taxpayer compliance. State revenue data comes from PPh 4 paragraph 2 specifically for MSMEs with PP. No. 46 of 2013 and PP No. 23 of 2018 over period of 4 years, namely 2016 to 2019. And using regression and path analysis. So that the results of this study indicate that the business profile is significant on taxpayer compliance, as well as the significant result between taxpayer compliance with state revenue, but business profile has no significant effect on State Revenue, the effect is direct, but the results differ if the effect of business profile on State Revenue through compliance. The result of taxpayers is significant. Â Â